May Subjective Language Complaints Predict Future Language Decline in Community-Dwelling Subjects? - Maruta, Carolina; Martins, Isabel Pavão (Frontiers in Psychology, 2019)
Subjective cognitive complaints are rather prevalent in the elderly population and are associated with an increased risk of cognitive impairment and dementia. However the predictive role of specific types of cognitive complaints has been less systematically assessed. The aim of the present study is to examine the predictive value of language complaints for cognitive and language decline in a cohort of community-dwelling healthy older adults, followed longitudinally over a 5-year period. A total of 402 subjects were enrolled in a prospective longitudinal study on Aging and Cognition. Participants answered a cognitive complaints questionnaire including two questions directed to Language and were classified at baseline as having “Language Complaints” (LC) or “No Language Complaints” (NLC). They also performed a neuropsychological assessment tackling attention/processing speed, memory, executive functioning and language at baseline. From these, 275 (68.4%), participated in a follow-up evaluation 4.9 (±0.6) years later. At re-evaluation, subjects had a mean age of 70.4 (±8.3) years, 7.5 (±4.4) years of education, and 63.3% were female. Multivariate linear regression analysis was used to investigate whether language complaints at baseline predicted poorer language performance at follow-up or increased the risk of cognitive decline, with correction for sex, depressive symptoms, living status, baseline performance and composite memory and executive performance. Results indicated that LC subjects had significantly worse performances than NLC subjects on semantic fluency 5 years later, but with a similar rate of decline overtime that was not associated with a follow-up outcome of cognitive decline/dementia. Language difficulties may represent a specific type of age related cognitive complaints. Longer follow-ups are necessary to understand if they are associated with an increased risk of language or cognitive decline.